Gastric Fibrinolysis - Nilsson, I. M; Bergentz, S.-E; Hedner, U; Kullenberg, K (Thrombosis and Haemostasis, 1975)
Gastric juice from 15 normals, 20 patients with gastric ulcer and 4 patients with erosive haemorrhagic gastroduodenitis was investigated in respect of its activity on unheated and heated fibrin plates and its content of FDP and plasminogen or plasmin with immunochemical methods. Gastric juice from normals showed no activity on unheated and heated fibrin plates, and no FDP or plasminogen could be demonstrated. In the patients with gastric ulcer the gastric juice showed little or no fibrinolytic activity on fibrin plates except in 2, who had regurgitation of duodenal juice and neutral pH of the juice. These patients had equally high activity on heated as on unheated plates and no plasmin could be demonstrated. It was shown that this activity was not due to fibrinolysis, but to non-specific proteolytic activity (probably trypsin). The patients with erosive haemorrhagic gastroduodenitis exhibited quite a different picture. The gastric juice from these patients showed extremely high activity on fibrin plates, the activity was higher on unheated than on heated plates. The activity was inhibited in vitro by addition of EACA and in vivo after administration of AMCA. The occurrence of plasmin could be demonstrated directly immunologically in the gastric juice. By comparison of plasmin and trypsin in various assays it could further be proved that the gastric juice in these cases contained plasminogen activator and plasmin. The patients with erosive haemorrhagic gastroduodenitis showed no increase in fibrinolysis in the blood, but low values for plasminogen and α2M, and the serum contained FDP. These findings in the blood and gastric juice were interpreted as signs of local fibrinolysis in the stomach and duodenum. There is reason to assume that this gastric fibrinolysis contributes substantially to the bleeding tendency. The effect of administration of AMCA on fibrinolytic activity and the haemorrhage lends support to the assumption of such a mechanism.